2012
DOI: 10.2174/156720512799015091
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated NF-κB Pathway in Peripheral Mononuclear Cells of Alzheimers Disease Patients

Abstract: Diagnosis and therapeutic strategies in Alzheimer's disease (AD) might greatly benefit of the present multidisciplinary approach for studying the molecular pathogenesis of the disorder. Gene expression profile at peripheral level could be a promising tool for pathogenic studies as well as for early diagnosis of AD. A dysregulated inflammatory response, as well as other systemic disorders, have been described in AD. Therefore, we investigated the expression, at peripheral level, of a number of genes involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Increasing evidence indicates that AD is characterized by multiple dysregulation at peripheral blood mononuclear cell level (Ascolani et al . ; Serini et al . ; Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that AD is characterized by multiple dysregulation at peripheral blood mononuclear cell level (Ascolani et al . ; Serini et al . ; Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the altered alternative splicing of mRAGE and esRAGE in PBMCs from AD patients Increasing evidence indicates that AD is characterized by multiple dysregulation at peripheral blood mononuclear cell level (Ascolani et al 2012;Serini et al 2012;Zhang et al 2012;Villa et al 2013). We investigated the expression of mRAGE and esRAGE at peripheral blood level during AD pathogenesis by analyzing the ratio of mRAGE and esRAGE variants in PBMCs from 7 AD patients and six healthy old people as the control.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Circulating mononuclear cells are mitotic cells, capable of proliferation. 42 In addition, proinflammatory/oxidant genes or transcription factor expression in PBMCs has been shown to increase under certain conditions such as old age and with cardiometabolic disorders such as hypertension, 43 Alzheimer disease, 44 and diabetic nephropathy. 45 However, the connection between exercise and oxidative stress or inflammation has long been debated.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that similar type of immune responses occur in the brain and periphery, and show the communication between the brain and peripheral immune systems. An interesting study demonstrated upregulation of nuclear factor-kappaB (NF-κB) activation in the peripheral blood mononuclear cells in AD patients thereby suggesting NF-κB inhibitors as therapeutic agents in AD patients (Ascolani et al, 2012). Imbalance of peripheral T cell subsets (decreased CD8 + and increased CD4 + cells) has been reported in AD patients indicating peripheral immune response in AD (Shalit et al, 1995); this is similar to a previous report on brain tumor patients that showed altered peripheral immune parameters in patients with a brain tumor (Kempuraj et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%